Repercussions of chronic hepatitis C treatment - Daniela Maria Falcão Oliveira; Juliano Souza Caliari; Ana Angélica Lima Dias; Rosely Moralez Figueiredo (Journal of Infection in Developing Countries)
Introduction: Individuals living with hepatitis C experience a series of changes in their lives, caused by either the disease itself or its treatment or both. In this sense, living with a chronic disease such as hepatitis C implies that patients must change their lifestyles, which requires that they rethink their habits in light of the new reality. To comprehend chronic hepatitis C patients’ perceptions, meanings, and quality-of-life effects. Methodology: Qualitative research; interviews with 12 patients at a specialized outpatient clinic from February to July 2012. The cohort size was determined by theoretical saturation and the interviews were analyzed by means of content analysis. Results: Data were organized into four categories: on medication, referenced fears, impact on sexuality, and coping with the new reality. The categorized data were discussed around the following themes: “Becoming sick” due to treatment and perceived aspects and Undergoing treatment and how to cope with it. Conclusion: Patients’ everyday lives and quality of life in general are affected especially by adverse side effects of hepatitis C medication and an assortment of feelings and uncertainties about the disease prognosis. Notwithstanding, most patients manage to find ways to cope with the treatment and complete it expecting a satisfactory outcome.